2004
DOI: 10.1007/s00436-004-1157-x
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of short-term in vitro cultivation for the detection and molecular study of Blastocystis hominis in stool specimens

Abstract: When in vitro cultivation was used as the 'gold standard' for the detection of Blastocystis hominis in stool specimens, simple smear and trichrome staining showed sensitivities of 16.7% and 40.2% and specificities of 94% and 80.4%, respectively. In vitro cultivation also enhanced PCR amplification for the detection of B. hominis in stool specimens. Our data show the usefulness of in vitro cultivation for the detection and molecular study of B. hominis in stool specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
42
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 11 publications
6
42
4
Order By: Relevance
“…The results from this study, with PCR being the most effective form of diagnosis, are consistent with those of studies that reported that molecular analysis is the most efficient method for detection of Blastocystis . 12,23 This finding is in contrast to those of another study, 20 which suggested that in vitro culture was superior to direct PCR for stool samples.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The results from this study, with PCR being the most effective form of diagnosis, are consistent with those of studies that reported that molecular analysis is the most efficient method for detection of Blastocystis . 12,23 This finding is in contrast to those of another study, 20 which suggested that in vitro culture was superior to direct PCR for stool samples.…”
Section: Discussioncontrasting
confidence: 79%
“…In addition, there have only been a few studies that compared the sensitivity of diagnostic techniques used for identification of Blastocystis sp. 20,21 Consequently, the aim of this study was to compare five diagnostic techniques (microscopy of a permanent stain using a modified ironhematoxylin stain, two xenic culture systems (modified Boeck and Drbohlav's medium [MBD] and tryptose, yeast extract, glucose, methionine 9 [TYGM-9] medium), and two published conventional PCR methods specific for the SSU rDNA) for detection of Blastocystis sp. in stool samples.…”
mentioning
confidence: 99%
“…In previous studies using Jones' medium supplemented with 10 % horse serum (Salim et al 1999 ;Leelayoova et al 2002 ;Suresh and Smith, 2004 ;Termmathurapoj et al 2004 ;Yakoob et al 2004 ;Yoshikawa et al 2004 c), only human faecal samples were screened for Blastocystis. However, several different types of media to cultivate Blastocystis have been reported, and it has been suggested that the usefulness of cultivation may depend on the reagents and protocols employed (Zaman and Khan, 1994 ;Leelayoova et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods used to detect Blastocystis infections, which include wet smears, concentration methods and in vitro amplification which was recently shown to be the most sensitive method to detect Blastocystis from faecal samples (Zaman and Khan, 1994 ;Leelayoova et al 2002 ;Suresh and Smith, 2004 ;Termmathurapoj et al 2004). However, due to the variable morphological forms that Blastocystis exhibits, it is impossible to distinguish among different species and subspecies of Blastocystis solely based on morphology without the use of molecular techniques (Yoshikawa et al 2004 b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation